2012
DOI: 10.17795/jjnpp-3504
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Poisoning in Southwestern Region of Iran: Envenoming as the Major Cause

Abstract: A B S T R A C TBackground: An analysis performed on the collected data from the Local Drug and Poison Information Centre (DPIC) of Jundishapur University revealed that stings are the main causes of poisonings with frequency of 56%, followed by drug poisoning in 31%, and chemical exposure poisoning in 5.5% in Khuzestan, the southwestern province of Iran. Objectives: The aim of the present study was to report the prevalence of poisoning in Khuzestan province referred to hospitals during the year 2007, on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
4
17
3
Order By: Relevance
“…In this study, majority of the poisoning cases presented between 15 and 40 year age group (59.2%).This is similar to a study conducted in Iran which reported that the 18-30 age group is more liable to poisoning (Jalali A et al,2012).This was in accordance with Zhou et al, 2005 who reported that at China emergency hospitals the age group between 15-34 years was the highest presentable age group and in an Indian study by Anthony and Kulkarni,2012 ,54.9% of cases were in the age group of 21-30 years. A possible explanation could be factors like financial, emotional, and social stresses.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, majority of the poisoning cases presented between 15 and 40 year age group (59.2%).This is similar to a study conducted in Iran which reported that the 18-30 age group is more liable to poisoning (Jalali A et al,2012).This was in accordance with Zhou et al, 2005 who reported that at China emergency hospitals the age group between 15-34 years was the highest presentable age group and in an Indian study by Anthony and Kulkarni,2012 ,54.9% of cases were in the age group of 21-30 years. A possible explanation could be factors like financial, emotional, and social stresses.…”
Section: Discussionsupporting
confidence: 90%
“…CNS depressants reported as the highest in the current study followed by analgesics. The same was found in a study in Iran which reported that CNS acting drugs were the commonest (Jalali A et al,2012 ), while Barrag and Farahat 2011 study reported paracetamol being the highest in Saudi Arabia . Also in the US the most frequent types of drug ingestion reported by poison centers during 2014 were analgesics (Mowry et al, 2015).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…When the data was analyzed by month, July was found to have the greatest number of admitted patients (14.6%).This is likely because it is the month when the most chemicals are used by farmers to increase their crop yield.An apparent decrease in the number of the patients was observed in March (2.6%), which is likely due to seasonal variation. In general more cases were reported during spring (28.8%) followed by the rainy and winter season (27.5% and 27% respectively), which was similar with other findings (Jalali et al 2012). However, other studies found the incidence during summer to be higher (Maharani et al2013).…”
Section: Discussionsupporting
confidence: 88%
“…Different poisoning situations exist across the cultures (Wananukul, Sriapha, Tongpoo, Sadabthammarak, Wongvisawakorn & Kaojarern, 2007) and it is an important health problem (Mutlu, Cansu, Karakas, Kalyoncu & Erduran, 2010).Poisoning comprehensive definition is available (Belson, Schier, Patel& Centers for Disease Control and Prevention (2005 (Jalali, Savari, Dehdardargahi & Azarpanah, 2012), agrochemical pesticides (49%), drugs (17%), alcohols (13%) (Singh &Unnikrishnan, 2006), anxiolytic/hypnotic drugs (lorazepam), acetaminophen (Lin, Liu, Liu, Chang, Chou & Wu, 2011), DSP, benzodiazepines (36.6%), paracetamol (22.2%), and antipsychotics (12.1%) (Cheri, Ramesh, Bhakta& Chris, 2012), sedative-hypnotics, opioids, pesticides organophosphates OPs (Shadnia, Esmaily, Sasanian, Pajoumand, Hassanian-Moghaddam&Abdollahi, 2007), alcohol (54.55%), medication (25.95%), pesticide (5.65%), drug (4.88%) (Chen, Wen, Wang, Lin & Lin, 2010), pharmaceuticals (63.1%), alcohol and surrogates (49.3%), and corrosives (21.8%) (Ostapenko, Matveev, Gassimova&Khonelidze, 2001).…”
Section: Introductionmentioning
confidence: 99%